An Overview of Career Maturity Among Grade XII-I Students at SMA Negeri 1 Pintu Pohan Meranti - Hannisa Heriadi; Priskila Adelisa Simbolon; Anika Sari Ayu; Jesslyn Novita Sibuea; Era Fazira (Insight: Journal of Counseling and Psychology, 2025)
Career planning is a crucial aspect of student development, as it determines future directions after completing secondary education. However, many students still demonstrate inadequate levels of career maturity, which hinders their ability to make career choices aligned with their interests and potential. This study aimed to analyze the level of career maturity among students at SMA Negeri 1 Pintu Pohan Meranti and to identify the aspects that most influence their readiness in making career decisions. A descriptive quantitative method was employed, involving 40 students as respondents who completed a 38-item Likert-scale questionnaire. The research instrument measured four dimensions of career maturity: career planning, career information exploration, informational competence, and career decision-making. Data were analyzed using descriptive statistics, including frequency and mean calculations, and total scores were classified into low, moderate, and high categories. The results revealed that 32.5% of students were categorized as having low career maturity, 35.0% as moderate, and 32.5% as high. These findings indicate that the majority of students exhibit low to moderate levels of career maturity, underscoring the importance of systematic and structured career guidance services in schools. This study provides practical implications for guidance and counseling teachers in designing more targeted and effective interventions to enhance students’ career maturity.